2014
DOI: 10.18388/abp.2014_1837
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation by random amplified polymorphic DNA-polymerase chain reaction (RAPD-PCR) of Candida albicans isolated from upper respiratory tract in patients with non-small cell lung cancer.

Abstract: Cancer patients are predisposed to fungal infections caused by Candida albicans, especially to oral or respiratory tract candidiasis. The aim of this study was to estimate genetic diversity by RAPD-PCR (random amplified polymorphic DNA-polymerase chain reaction) of C. albicans isolated from upper respiratory tract of 100 patients with non-small cell lung cancer. Among 52 strains, 34 genotypes were defined. 10 clusters comprising 28 (53.85%) isolates with similarity coefficient ≥ 80% were formed. The remaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…As the resistance of C. albicans to antifungal drugs commonly used in local and general treatment is increasing, it is necessary to look for simple and adverse affects-free prophylactic and therapeutic means to counteract the increase (11). In the case of oral cavity mycoses, an alternative to conventional antimycotics may be chlorhexidine which, as research confirmed, shows antifungal activity in vivo and in vitro (25).…”
Section: Discussionmentioning
confidence: 99%
“…As the resistance of C. albicans to antifungal drugs commonly used in local and general treatment is increasing, it is necessary to look for simple and adverse affects-free prophylactic and therapeutic means to counteract the increase (11). In the case of oral cavity mycoses, an alternative to conventional antimycotics may be chlorhexidine which, as research confirmed, shows antifungal activity in vivo and in vitro (25).…”
Section: Discussionmentioning
confidence: 99%
“…Cancer patients are predisposed to fungal infections caused by Candida albicans , especially oral or respiratory tract candidiasis. Biernasiuk and colleagues [ 30 ] applied RAPD-PCR to successfully estimate genetic diversity of C. albicans isolated from the upper respiratory tract of patients with non-small cell lung cancer. However, there are some disadvantages to RAPD, like poor reproducibility and low yield of PCR products (low production).…”
Section: Discussionmentioning
confidence: 99%